In vitro evaluation of Eugenia dysenterica in primary culture of human gingival fibroblast cells - Cláudio Rodrigues Rezende Costa; Bruna Rabelo Amorim; Sandra Márcia Mazutti da Silva; Ana Carolina Acevedo; Pérola de Oliveira Magalhães; Eliete Neves Silva Guerra (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract: Eugenia dysenterica is a Brazilian tree investigated for its properties and bioactive compounds, which are believed to have both pharmacological and phytochemical therapeutic effects. The leaves of this tree contain tannins, flavonoids, terpenes, and saponins, with reportedly beneficial effects to the human body. Despite these therapeutic applications, its effects have never been tested on oral tissues. Therefore, the aim of the present study was to evaluate the cytotoxic and antioxidant effects and the anti-inflammatory and repair properties of the acetone fraction of E. dysenterica on primary culture of human gingival fibroblasts and on the immortalized murine macrophage cell line (RAW 264.7). For this purpose, a metabolic activity assay, a wound healing assay, a nitric oxide assay, and RT-qPCR were performed. The assays revealed a cytoprotective effect of this plant, suggested by the increase in the expression of SOD1 and NRF2. An antioxidant potential effect was observed in the DPPH• assay. However, the fraction of E. dysenterica did not show anti-inflammatory activity. In conclusion, Eugenia dysenterica may promote cytoprotection when associated with chlorhexidine digluconate because of its antioxidant effect. However, additional studies are necessary on other human dental tissues using other parts of the plant in order to develop a possible mouthwash to assist patients with oral disorders.